An Examination of the Impact of State Governance on Foreign Direct Investment in Vietnam - Pereira, Stephen (Journal of Asian Business Strategy, 2013)
1986 marked the start of Vietnam‟s „Doi Moi‟ or period of renovation. During this time, Vietnam began to liberalize their economy and began to open and globalize the country. For the first time the government encouraged foreign direct investment, and allowed the creation of non-state controlled businesses. Later becoming part of the World Trade Organization in 2007, the „renovation‟ of Vietnam continued to progress. Though improving significantly, Vietnam still lacks effective state governance. This paper examines the relationship between state governance and degree of foreign direct investment. Using linear regression techniques, 20 years of foreign direct investment data, and a specific state governance dataset, this paper begins define that relationship. The results show that looking back in the long term there is no significant relationship between the quality of government and number of foreign direct investment projects. However, looking back in the short term, a positive significant relationship is found between the quality of governance and number of licensed FDI projects a year.